Handbook of Exoplanets 2017
DOI: 10.1007/978-3-319-30648-3_37-1
|View full text |Cite
|
Sign up to set email alerts
|

Transiting Disintegrating Planetary Debris Around WD 1145+017

Abstract: More than a decade after astronomers realized that disrupted planetary material likely pollutes the surfaces of many white dwarf stars, the discovery of transiting debris orbiting the white dwarf WD 1145+017 has opened the door to new explorations of this process. We describe the observational evidence for transiting planetary material and the current theoretical understanding (and in some cases lack thereof) of the phenomenon. OverviewA bit more than a decade after astronomers first began to suspect that whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Gänsicke et al 2016;Gary et al 2017;Croll et al 2017). The origin, creation mechanism, and lifetimes of these orbiting bodies are currently uncertain at best, with inferred masses in the range of 10 17 − 10 24 g (Vanderburg et al 2015;Rappaport et al 2016). Additional dynamical simulations support the statement that the orbiting objects should be no more massive than Ceres (Gurri et al 2017).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Gänsicke et al 2016;Gary et al 2017;Croll et al 2017). The origin, creation mechanism, and lifetimes of these orbiting bodies are currently uncertain at best, with inferred masses in the range of 10 17 − 10 24 g (Vanderburg et al 2015;Rappaport et al 2016). Additional dynamical simulations support the statement that the orbiting objects should be no more massive than Ceres (Gurri et al 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Followup observations came quickly (e.g. Gänsicke et al 2016;Rappaport et al 2016;Gary et al 2017;Croll et al 2017) and found that the transit durations range from ∼ 3 min to as long as an hour-much longer than expected for a solid body ( Vanderburg et al 2015). The transits are inferred to be caused by the passage of dust clouds rather than solid bodies.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations